2022
DOI: 10.1155/2022/8454865
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Anti-Inflammatory and Antioxidant Activities of Bamboo Sasa albomarginata Leaf Extract and Its Constituent Coumaric Acid Methyl Ester

Abstract: Background. Hot water extract of Sasa albomarginata (Kumazasa) leaves is commercially available and used as a dietary supplement or skincare cream. The extract possesses anti-inflammatory activity on the mouse atopic dermatitis model. To elucidate the mechanism of in vivo activity, we have studied the cellular anti-inflammatory and antioxidant activities of the extract and its constituents. Methods. Secretion of mouse and human IL-6 was measured by ELISA. ROS production was measured by a fluorescent reagent. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recently, it has been reported that bamboo extracts from Sasa albomarginata are able to inhibit LPS-induced inflammatory responses at nontoxic concentrations in macrophages [ 22 ]. Thus, we aimed to explore the potential anti-inflammatory activities of bamboo extracts from Phyllostacys edulis, using LPS-stimulated humanmacrophages, as an in vitro model of acute inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that bamboo extracts from Sasa albomarginata are able to inhibit LPS-induced inflammatory responses at nontoxic concentrations in macrophages [ 22 ]. Thus, we aimed to explore the potential anti-inflammatory activities of bamboo extracts from Phyllostacys edulis, using LPS-stimulated humanmacrophages, as an in vitro model of acute inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-inflammatory activities of bamboo leaf extracts specifically have been described in different cellular contexts [ 22 , 23 , 24 ]. Despite the growing identification of chemical compounds in bamboo, most of the pharmacological studies have focused on bamboo leaf flavonoids [ 19 ].…”
Section: Introductionmentioning
confidence: 99%